Circular RNA circCRIM1 inhibits invasion and metastasis in lung adenocarcinoma through the microRNA (miR)‐182/miR‐93‐leukemia inhibitory factor receptor pathway. Issue 9 (14th August 2019) - Wang, Lin; Liang, Yingkuan; Mao, Qixing; Xia, Wenjie; Chen, Bing; Shen, Hongyu; Xu, Lin; Jiang, Feng; Dong, Gaochao
Abstract: In recent years, circular RNAs (circRNAs) have been revealed to have important roles in carcinogenesis. Metastasis is the leading cause of lung adenocarcinoma (LUAC) death. However, the contributions of circRNA to the metastasis of LUAC remain largely unknown. Based on circBase data and our biobank tissues, we identified circCRIM1 (a circRNA derived from exons 2, 3 and 4 of the CRIM1 gene, hsa_circ_0002346) as having a significantly decreased expression in LUAC samples compared with matched normal control samples. Both in vivo and in vitro experiments revealed that circCRIM1 suppresses the invasion and metastasis of LUAC. In vitro precipitation of circRNAs, luciferase reporter assay, and biotin‐coupled microRNA capture were carried out to investigate the Ago2‐dependent interaction of circCRIM1 and microRNA (miR)‐93/miR‐182. Mechanistically, we found that circCRIM1 could promote the expression of leukemia inhibitory factor receptor, a well‐known tumor suppressor, by sponging miR‐93 and miR‐182. In the clinical and pathological analyses, the downregulation of circCRIM1 in LUAC was significantly correlated with lymphatic metastasis and TNM stage, which served as an independent risk factor for the overall survival of patients with LUAC. Our study showed that circCRIM1 inhibits the invasion and metastasis of lung adenocarcinoma cancer cells, which makes it a potential therapeutic target. Abstract : Upregulation of circCRIM1 exerts the invasion‐suppression effect dependent on the circCRIM1‐microRNA‐182/93‐leukemia inhibitory factor receptor axis.